한국 치과기공사의 인력수급 - 이병기 (연세대학교 보건대학원, 1985)
[한글] 본 연구는 우리나라 치과기공사의 현재와 미래에 있어 합리적이며 경제적인 치과의료써비스를 효율적으로 제공하기 위한 인력계획의 일환으로 치과기공사의 적정 수급계획 수립에 참고자료가 되기 위해 연구·.분석하였다. 조사대상은 1965년부터 1985년 현재까지 보건사회부에 등록된 치과기공사 3,885명 전체를 조사대상으로 하였다. 조사내용은 우리나라 치과기공사의 현황분석과 외국의 치과기공사의 현황분석을 하고 우리나라 추계인구및 1인당 국민소득을 추계분석 조사하여 시행하였다. 분석방법은 우리나라 치과기공사의 수요추계 방법으로서 첫째 우리나라 치과의사 비례에 의한 치과기공사의 수요추계, 둘째 전 세계및 선진국 평균 수준에 따른 인구 비례에 의한 수요추계, 셋째 우리나라 1인당 국민소득 수준에 따른 치과기공사의 수요추계의 3가 지 방법으로 치과기공사의 수요추계 모형을 만들어 산출하였다. 또한 치과기공사 공급추계 방법으로는 현재 양성 능력기준으로한 치과기공사 공급추계 모형을 만들어 산출하였다. 조사성적을 요악하면 다음과 같다. 1) 우리나라 치과기공사의 교육기관은 14개 보건전문대학이 있으며 보건사회부에 면허 등록된 치자기공사중 수술기관에서 779(20.0%)명, 교육기관에서 3,106(79.9%)명이 배출되어 총 3,885명의 치과기공사가 있다. 2) 1965년 이후 22회에 걸쳐 의료기사 치과기공사 국가시험을 시행하여 총 8,030명이 응시하여 48.3%인 3,885명이 최종합격 하였다. 3)우러나라 치과기공사의 취업기관은 치과기공소 404개소, 치과병의원 2,522개소가 있고 서울·부산에 치과기공소 255(63.1%)개소, 치과병의원 1,537(60.9%)개소가 집중되어 있다. 4) 우리나라 치과기공사의 취업실태는 2,160명중 1,126(52.1%)명, 미취업 530(24.5%)명, 군복무, 해외, 기타 행방불명이 504(23.3%)명으로 나타났다. 5) 외국의 치과기공사는 1973∼1977년에 전세계는 95,886명으로 인구 10만명당 9.04명, 선진국에는 91.553명으로 인구 10만명당 13.92명으로 나타났고, 치과의사 1명당 치과기공사의 비율은 평균 0.38명으로 나타났다. 또한 인구 10만명당 및 국민소득 $100당 치과 기공사는 평균 0.272명으로 나타났다. 6) 1985년부터 1996년까지의 우리나라 치과기공사의 연도별 수요와 공급을 추계한 결과 현재 양성능력 기준으로한 공급은 우리나라 향후 국민소득에 따른 수요와 치과의사 추계비례에 의한 수요보다 공급과잉이 되겠고, 전세계 평균 수준에 따른 인구비례에 의한 수 요도 1988년부터는 공급과잉으로 나타났다. 또한 선진국 수준에서의 수요는 공급이 부족했으나 1994년부터는 역시 공급과잉으로 되었다. [영문] In order to provide the better and more effective dental health service, the study for manpower of dental laboratory technician with some relevant factors such as institutions for education and training, employment status and distribution of technicians, etc. was carried out through survey for 3,885 licensed technicians ducting 1965-1985. Results were obtained through the study as follows : 1. There are 14 junior health colleges in Korea and 3,106(79.9%) licensed dental technicians 7ut of 3,885 graduated from health colleges and rest of them obtained their licenses through practical training in dental clinics. 2. 8,030 applicants have applied to the national examination which was carried but for 22 times during 1965-1985. The passing rate in the examination for 22 times showed 48.3% in average. 3. The dental technicians are working mos시y in 404 dental laboratories and 2,522 dental clinics and hospitals through out the country. However, most technicians are dominantly working in large cities, because 255(63.1%) dental laboratories and 1,537 (60.9%) dental clinics and hospitals are mainly located in Seoul and Busan. 4. Regarding distribution of the dental technician. 1,126(52.1%) technicians have been employed in the dental institutions, however, 530(24.5%) could not have a job and the rest of them (504 technicians : 23.3%) were in leave of absence from military service, travelling abroad and unknown reasons. 5. Through reference review, it was found that there were 95,886 dental technician (9/100,000 population) in the world during 1973-1977. However, 91,553 dental technicians lived in the developed countries (14/100,000 population) also ratio between the dentist and the dental technician in the world skewed 1 : 0.38. In such countries where per capita income showed $100 in average, the distribution of the dental technician showed 0.272 per 100,000 population. 6. In an estimation of demand and supply for the dental technicians by the year from 1985 through 1996 in Korea, the supply is estimated by the capacity of educational institutions as over-production even though such estimation based on the future increasing of GNP and ratio between the dentist and the dental technician and also ratio between the dental technician and general population. At present such ratio shows less compared with the developed countries, however, it is estimated as over-supply in 1994.
보건학과/석사